The Hut-Hospital as Project and as Practice. Mimeses, Alterities, and Colonial Hietatchies - Bastos, Cristiana (2018)
This article analyzes one kind of colonial equipment designed in the early twentieth century for the purpose of providing medical assistance to the indigenous populations of Angola and Mozambique. I will refer to it as a ‘hut-hospital’, although it had several forms and designations. The layout of hut-hospitals consisted of a main building and a number of hut-like units that were supposedly more attractive to the indigenous population and therefore more efficient than the large, rectangular buildings of the main colonial hospitals. Using different sources, including three-dimensional plaster models of hut-hospitals, photographs, legal documents, and 1920s conference papers and articles, I will investigate the relatively obscure history of this colonial artifact while exploring the use of imitation as part of the repertoire of colonial governance.